The determination of induction motor losses in steel taking into account its saturation. Issue 2 (5th January 2022) - Zagirnyak, Mykhaylo; Ogar, Vita; Chenchevoi, Volodymyr; Yatsiuk, Rostyslav
Abstract : Purpose: This paper aims to work out a method for calculating losses in induction motor steel taking into account its saturation. Design/methodology/approach: The theory of electric machines is applied during the analysis of induction motor equivalent circuits. The theory of Fourier series is used to determine the harmonic components of voltage, current and power. Instantaneous power theory and trigonometric transformations are used to solve algebraic and differential equations and their systems. The methods of approximation and interpolation are applied to obtain analytical expressions from the experimental data. Experimental research was carried out to verify the reliability of theoretical provisions and research results. Findings: A method for assessing an induction machine steel as a function of the generalized electromotive force has been proposed. It allows taking into account higher harmonics of the current, which are caused by the presence of nonlinearity of an induction motor magnetic circuit. Practical implications: The obtained results can be used in calculating the energy characteristics and operating modes of an induction motor, as well as in the construction of control systems. Originality/value: A method for determining the losses in the stator steel of an induction motor, using a generalized electromotive force, has been proposed for the first time. It enables taking into account the currents flowing both in the stator circuit and in the rotor circuit.